Digitalization Of Kedai Industry: Analysis of The Role of Internet Marketing Orientation and Innovation on Marketing Performance - Darmawan, Didit; Sari, Putri Nur Laila; Jahroni, Jahroni; Halizah, Siti Nur; Mardikaningsih, Rahayu (Sustainable Environmental and Optimizing Industry Journal, 2023)
The digitization of the store industry has become an increasingly important trend in today's digital era, and internet marketing orientation and innovation are considered key factors in achieving competitive advantage in a digital environment. This study aims to analyze the role of internet marketing orientation and innovation in digitizing the shop industry and its impact on marketing performance. This study used a quantitative analysis method using primary data collected through a survey of shop owners and managers in Waru District, Sidoarjo Regency, East Java. The research sample consists of 50 shops that have carried out the digitization process. Sampling used accidental sampling which was then analyzed with multiple linear regression. The results of the analysis show that internet marketing orientation and innovation have a significant positive effect on marketing performance in the digitalization of the tavern industry. More specifically, the effective use of social media and e-commerce platforms increases the visibility and accessibility of stores, thereby increasing the number of customers and sales volume. In addition, product and process innovation in store digitization can increase differentiation and operational efficiency, which in turn affects customer satisfaction and business profits.